Synthesis of the New 1-(7-Methoxy-1-benzofuran-2-yl)-3-(4-methylphenyl)prop-2-en-1-one and Controlling of Spectroscopic, Optical and Conductivity Properties by Concentration - Coskun, Demet; Coskun, Mehmet Fatih; Gunduz, Bayram (Slovensko Kemijsko Drustvo, 2022)
Chalcone derivatives have an important place in science due to their different applications ranging from their semiconductor properties to biological properties. In this work 1-(7-methoxy-1-benzofuran-2-yl)-3-(4-methylphenyl)prop-2-en-1-one (2) has been prepared by condensation of 1-(7-methoxy-1-benzofuran-2-yl)ethanone with 4-methylbenzaldehyde in basic medium. The chemical structure of 2 was confirmed by elemental analysis, FT-IR, H-1 NMR and C-13 NMR. UV spectroscopic characteristics, absorption band edges, optical band gaps, refractive indices, environmental behaviors and conductivity properties of 2 in solutions at different concentrations were investigated in detail. With the concentration, we examined how the spectroscopic, optical and conductivity properties of 2 have changed and can be controlled.
Keywords: Benzofuran; chalcone; absorption band edge; optical band gap; refractive index; environmental behavior; conductivity properties